Pharmaceutical treatment of asthma symptoms in elite athletes - doping or therapy? - Backer, V.; Lund, T.; Pedersen, L. (Scandinavian Journal of Medicine & Science in Sports, 2007)
Asthma, exercise-induced bronchoconstriction, and airway hyper-responsiveness are often found in elite athletes, perhaps as a consequence of their sport or maybe because asthma is a common disorder in young adults. Inhaled ß2-agonists (IBA) are frequently used in elite athletes, but due to regulations introduced by the International Olympic Committee, the use of anti-asthmatic therapy might change. Drugs that make ergogenic effect persist are prohibited in all athletes, whether or not they take part in competitions and systemic steroids and ß2-agonists are among such drugs. On the other hand, opinion is more divided about the use of inhaled corticosteroids (ICS) and IBA. In humans, no effect has been found on the oxygen uptake, performance or distance run with therapeutic doses of IBA, either in asthmatics or non-asthmatics, whereas others report an ergogenic effect and better lung function of high doses of a ß2-agonist in non-asthmatics. Anti-asthmatic treatment is necessary for asthmatics, but should not be used by non-asthmatic elite athletes due to both possible systemic effects and furthermore, side effects of both ICS and IBA.